Efficacy and Safety of Sofosbuvir/Velpatasvir/Voxilaprevir for Hepatitis C Virus (HCV) NS5A-Inhibitor Experienced Patients With Difficult to Cure Characteristics. (5th September 2020) - Papaluca, Timothy; Roberts, Stuart K; Strasser, Simone I; Stuart, Katherine A; Farrell, Geoffrey; MacQuillan, Gerry; Dore, Gregory J; Wade, Amanda J; George, Jacob; Hazeldine, Simon; O'Beirne, James; Wigg, Alan; et al.
Abstract: Background: In clinical trials, hepatitis C virus (HCV) salvage treatment with sofosbuvir/velpatasvir/voxilaprevir (SOF/VEL/VOX) achieved an SVR12 rate of >95% in NS5A-experienced participants. Lower SVR12 rates have been reported in real-world studies, particularly for genotype (GT)3 infection and cirrhosis. We determined the efficacy and safety of SOF/VEL/VOX in a large real-world cohort. Methods: We assessed the efficacy of salvage SOF/VEL/VOX for HCV infection in NS5A-inhibitor experienced participants with cirrhosis and portal hypertension, prior liver transplantation (LT) or severe extra-hepatic manifestations. SOF/VEL/VOX was available via an early access program. The primary outcome was SVR12. Secondary outcome was frequency of adverse events (AE). Findings: Ninety-seven participants were included. Median age was 58, 82% were male, 78% had cirrhosis, most with portal hypertension (61%, n = 46/76), and 18% had prior-LT. Of the cirrhotic participants, 96% were Child-Turcotte-Pugh class A, and 4% were class B. Of the 72% with GT3, 76% were also cirrhotic. By intention-to-treat analysis, SVR12 rate was 85% (n = 82/97). Per protocol, the SVR12 rate was 90%, including 91% in GT1 (GT1a n = 18/18, GT1b n = 2/4), 89% in GT3 (n = 59/66) and 100% in GT6 (n = 3/3). SVR12 in participants with GT3 and cirrhosis was 90%. No predictors of non-SVR12 were identified. There were 4 serious AEs including 1 death and 3 hepatic decompensation events. NS5A resistance-associated substitutions detected at baseline did not affect SVR12. Conclusions: This real-world study confirms high efficacy of SOF/VEL/VOX for the treatment of difficult-to-cure NS5A-inhibitor experienced patients, including those with GT3 and cirrhosis. Treatment was well tolerated in most; however, serious AEs can occur in those with advanced liver disease. Abstract : Sofosbuvir/velpatasvir/voxilaprevir achieved high SVR12 rates in NS5A-inhibitor experienced participants irrespective of difficult to cure characteristics including genotype 3 infection, cirrhosis, portal hypertension or prior liver transplantation. Treatment was generally safe, however those with advanced liver disease should be monitored carefully.